Flannery O'Connor, Hermit Novelist - Candler, Peter (Literature and theology, 2002)
Flannery O'Connor, Hermit Novelist RichardGiannone ChicagoUniversity of Illinois Press 2000x + 287£29.95 $35 , 1University of Cambridge